Again and Again and Again: Music as Site, Situation and Repetition - Buene, Eivind (Oslo Norges musikkhøgskole, 2018)
Again and Again and Again is about new musical works that in various ways integrate historical music as important components. The texts were written during Eivind Buene's fellowship in The Norwegian Artistic Research Programme, where he investigated the critical potential in the repetition of music history, working with the historical residue in the apparatus of production and performance of new music. Through the emergence of advanced technology of storage and reproduction in the twentieth century, the function of historical memory has changed, something that has been thoroughly dealt with in fine arts and in critical theory. Repetition is a central term in works where new practices relive old ones and simultaneously make these strategies the object of critical scrutiny. In music, this harbours an approach to the artistic material where the institutions, places, formats and situations of music become material as much as pitch, duration and timbre. According to these interests, Buene composed three works during the project period: a piece for orchestra and electronics made within the framework of the orchestral performance the symphonic site; a work where the situation of chamber music performance was thematized; and a performance where the intimacy of the private musical space has been investigated. These works are reflected in this body of text, where ideas in and around the works are discussed in three different formats: the essay, the brief note and excerpts from two of Buenes novels, written in conjunction with his artistic research.
Keywords: Music philosophy and esthetics